A multilingual sexual and reproductive health animation: a novel educational tool for newcomer patients - Sivakumar, Aditi; Willows, Karla; Behroozan, Sepideh; Stairs, Jocelyn (Canadian Medical Education Journal, 2023)
Implication Statement Newcomer populations face many barriers accessing healthcare, including language barriers. Language-concordant care has been shown to enhance equity and optimize health outcomes for underserved populations. This paper describes a sexual and reproductive health (SRH) animation for newcomer populations. The animation was created collaboratively by the Department of Obstetrics and Gynaecology Global Health Unit, the Halifax Newcomer Health Clinic, and student volunteers. Integrating this animation into other healthcare settings may help improve inclusion, trust, and patient-centred care for newcomer patients. Institutions may also consider creating further SRH animations based on the needs of the patients they serve.